Response of Organ Structure and Physiology to Autotetraploidization in Early Development of Energy Willow Salix viminalis - Dudits, Dénes; Török, Katalin; Cseri, András; Paul, Kenny; Nagy, Anna V; Nagy, Bettina; Sass, László; Ferenc, Györgyi; Vankova, Radomira; Dobrev, Petre; Vass, Imre; Ayaydin, Ferhan (Plant physiology, 2016)
The biomass productivity of the energy willow Salix viminalis as a short-rotation woody crop depends on organ structure and functions that are under the control of genome size. Colchicine treatment of axillary buds resulted in a set of autotetraploid S. viminalis var. Energo genotypes (polyploid Energo [PP-E]; 2n = 4x = 76) with variation in the green pixel-based shoot surface area. In cases where increased shoot biomass was observed, it was primarily derived from larger leaf size and wider stem diameter. Autotetraploidy slowed primary growth and increased shoot diameter (a parameter of secondary growth). The duplicated genome size enlarged bark and wood layers in twigs sampled in the field. The PP-E plants developed wider leaves with thicker midrib and enlarged palisade parenchyma cells. Autotetraploid leaves contained significantly increased amounts of active gibberellins, cytokinins, salicylic acid, and jasmonate compared with diploid individuals. Greater net photosynthetic CO2 uptake was detected in leaves of PP-E plants with increased chlorophyll and carotenoid contents. Improved photosynthetic functions in tetraploids were also shown by more efficient electron transport rates of photosystems I and II. Autotetraploidization increased the biomass of the root system of PP-E plants relative to diploids. Sections of tetraploid roots showed thickening with enlarged cortex cells. Elevated amounts of indole acetic acid, active cytokinins, active gibberellin, and salicylic acid were detected in the root tips of these plants. The presented variation in traits of tetraploid willow genotypes provides a basis to use autopolyploidization as a chromosome engineering technique to alter the organ development of energy plants in order to improve biomass productivity.
Keywords: biomasa; listy rostlin; fenotyp; Phenotype; kůra rostlin; genom rostlinný; duplikace chromozomů; Genome, Plant; fotosyntéza; Genotype; konfokální mikroskopie; Biomass; dřevo; Photosynthesis; Plant Roots; Chlorophyll; Salix; regulátory růstu rostlin; stonky rostlin; chromozomy rostlin; Wood; Chromosomes, Plant; Plant Stems; kořeny rostlin; Chromosome Duplication; Microscopy, Confocal; Plant Bark; chlorofyl; Plant Growth Regulators; Carotenoids; Plant Leaves; tetraploidie; Diploidy; genotyp; Tetraploidy; diploidie; karotenoidy